Evaluating the Effectiveness of Integrated Online English Learning Models in Information Systems Study Programs - Mike Amelia; Fitri Handayani (Journal of English Language Learning, 2026)
The rapid digital transformation of higher education has increased the need for effective technology-enhanced English learning, particularly for Information Systems students who must access technical documentation, academic resources, and professional communication in English. This study evaluated the effectiveness of an integrated online English learning model in an Information Systems Study Program at Bina Sarana Informatika University. A mixed-method design was employed with 42 undergraduate students enrolled in an English course. Data were collected through pre-tests, post-tests, questionnaires, observations, and semi-structured interviews. Quantitative data were analyzed using descriptive statistics and a paired-sample t-test, while qualitative data were analyzed thematically. The model was implemented through the MyBest Learning Management System, multimedia resources, online discussions, video conferencing, and interactive assessments. The findings indicated positive student perceptions, particularly regarding access to learning materials (M = 4.48), learning flexibility (M = 4.42), and overall satisfaction (M = 4.25). Students’ mean English scores increased from 67.4 in the pre-test to 83.6 in the post-test, and the improvement was statistically significant (p < 0.05). The greatest improvement occurred in technical vocabulary, followed by reading, listening, writing, and speaking skills. Qualitative findings showed that multimedia resources, online collaboration, and flexible learning enhanced engagement, motivation, and self-regulated learning. However, challenges included internet connectivity, limited concentration, reduced interaction in some activities, and differences in digital literacy. Overall, the integrated online English learning model effectively improved students’ English achievement and provided a flexible, engaging, and learner-centered learning environment. These findings support wider use of digital learning in technology-oriented higher education programs.